ОСОБЕННОСТИ ЭФФУЗИВНОГО ПЕРИКАРДИТА КАК ПОЗДНЕГО ОСЛОЖНЕНИЯ ПРИ COVID-19 И НЕКОТОРЫЕ ЕГО ФАРМАКОТЕРАПЕВТИЧЕСКИЕ АСПЕКТЫ (Клинический Случай) / THE FEATURES OF EFFUSIVE PERICARDITIS AS A LATE COMPLICATION OF COVID-19 AND SOME PHARMACOTHERAPY MANAGEMENT ASPECTS (Case Report) - Patsia, Lali; Lartsuliani, Ketevan; Sulashvili, Nodar; Beglaryan, Margarita; Gabunia, Luiza; Gorgaslidze, Nana (Bulletin of the Medical Institute after Mehrabyan, 2023)
Мы рассмотрели редкий случай острого перикардита с перикардиальным выпотом у 44-летнего мужчины с диагнозом COVID-19 за месяц до перикардита. У него были респираторные симптомы и положительный тест на COVID-19 за 4 недели до обращения в нашу больницу по поводу дискомфорта в груди и одышки, тахикардии, учащенного дыхания. Мы предполагаем, что у этого пациента был перикардит с выпотом в перикарде как отсроченное осложнение COVID-19, поскольку при поступлении у него был положительный результат полимеразной цепной реакции на COVID-19, и никакое другое случайное заболевание или инфекция не могли вызвать его симптомы. Хотя мы не фиксировали уровень провоспалительных цитокинов, неспецифические маркеры воспаления, такие как D-димер и С-реактивный белок, были повышены, что свидетельствует о воспалении. Ему была начата стандартная терапия перикардита – ибупрофен + колхицин, с улучшением симптомов. Во время пребывания в больнице его лейкоцитоз разрешился, уровень СРБ снизился, а боль в груди значительно уменьшилась. Этот случай подчеркивает важность продолжения расследования диагностики и лечения COVID-19 и связанных с ним симптомов. Целью данного описания случая является повышение осведомленности медицинского сообщества о возможности осложнений со стороны сердца на длительной фазе Covid-19. / We report a rare case of acute pericarditis presenting with pericardial effusion in a 44-year-old man diagnosed with COVID-19 one month prior to pericarditis. He had respiratory symptoms and a positive test for COVID-19 4 weeks before presentation to our hospital for chest discom-fort and shortness of breath, tachycardia, tachypnea. We propose that this patient had pericardi-tis with pericardial effusion as a delayed complication of COVID-19 because he was COVID-19 positive by polymerase chain reaction during admission and no other coincidental illness or infection could have caused his symptoms. Although we did not capture the level of proin-flammatory cytokines, nonspecific markers of inflammation such as D-dimer and C-reactive protein were elevated, suggestive of inflammation. He was initiated with standard therapy for pericarditis – ibuprofen +colchicine, with improvement in his symptoms. During his hospital course, his leukocytosis resolved, CRP levels decreased, and chest pain significantly improved. This case emphasizes the importance of continued investigation regarding diagnosis and treat-ment of COVID-19 and its related symptoms. The aim of this case report is to raise awareness in the medical community on the possibility of complications targeting heart in the long-COVID-19 phase.